Yield and Water Productivity Responses to Irrigation Cut-off Strategies after Fruit Set Using Stem Water Potential Thresholds in a Super-High Density Olive Orchard - Ahumada-Orellana, Luis E.; Ortega-Farías, Samuel; Searles, Peter S.; Retamales, Jorge B. (Frontiers in Plant Science, 2017)
An increase in the land area dedicated to super-high density olive orchards has occurred in Chile in recent years. Such modern orchards have high irrigation requirements, and optimizing water use is a priority. Moreover, this region presents low water availability, which makes necessary to establish irrigation strategies to improve water productivity. An experiment was conducted during four consecutive growing seasons (2010-2011 to 2013-2014) to evaluate the responses of yield and water productivity to irrigation cut-off strategies. These strategies were applied after fruit set using midday stem water potential (Ψstem) thresholds in a super-high density olive orchard (cv. Arbequina), located in the Pencahue Valley, Maule Region, Chile. The experimental design was completely randomized with four irrigation cut-off treatments based on the Ψstem thresholds and four replicate plots per treatment (five trees per plot). Similar to commercial growing conditions in our region, the Ψstem in the T1 treatment was maintained between -1.4 and -2.2 MPa (100% of actual evapotranspiration), while T2, T3 and T4 treatments did not receive irrigation from fruit set until they reached a Ψstem threshold of approximately -3.5, -5.0, and -6.0 MPa, respectively. Once the specific thresholds were reached, irrigation was restored and maintained as T1 in all treatments until fruits were harvested. Yield and its components were not significantly different between T1 and T2, but fruit yield and total oil yield, fruit weight, and fruit diameter were decreased by the T3 and T4 treatments. Moreover, yield showed a linear response with water stress integral (SΨ), which was strongly influenced by fruit load. Total oil content (%) and pulp/stone ratio were not affected by the different irrigation strategies. Also, fruit and oil water productivities were significantly greater in T1 and T2 than in the T3 and T4. Moreover, the T2, T3 and T4 treatments averaged 37, 51 and 72 days without irrigation which represented 75-83, 62-76 and 56-70% of applied water compared with T1, respectively. These results suggest that using the T2 irrigation cut-off strategy could be applied in a super-high density olive orchard (cv. Arbequina) because it maintained yields, saving 20% of the applied water.